A study of sleep hygiene practices and quality of sleep in health professional students - Neha D. Gawade; David N. Isaac; Rita M. Khadkikar; Catherine D. Isaac (MGM Journal of Medical Sciences)
Background: Chronic sleep deprivation is a prevalent yet treatable condition among young adults and teenagers, often resulting from various sleep disorders that negatively affect overall wellbeing in this age group. Sleep quality refers to an individual’s overall satisfaction with different aspects of their sleep experience, while sleep hygiene encompasses easily modifiable pre-sleep behaviors that support healthy sleep patterns. This study aims to assess health professional students’ sleep quality and hygiene practices and evaluate the correlation between these two factors. Materials and Methods: This prospective, observational, and cross-sectional study involved 320 health professional students who completed a self-administered questionnaire. The Pittsburgh sleep quality index(PSQI) was used to assess sleep quality, while the sleep hygiene index (SHI) was used to evaluate sleep hygiene practices. Data were recorded in Excel and analyzed by a statistician. Results: Of the 320 participants, 74.4% (238 students) exhibited a moderate SHI, 13.4% (43 students) had a fair SHI, 11.6% (37 students) demonstrated excellent sleep hygiene, and 0.6% (2 students) showed poor sleep hygiene. Additionally, 63.8% (204 students) reported poor sleep quality, while 36.3% (116) experienced good sleep quality. Conclusion: Most health professional students followed moderate sleep hygiene practices and reported poor sleep quality. Statistical analysis revealed a significant positive correlation between sleep hygiene and sleep quality, suggesting that improving sleep hygiene practices may lead to better sleep quality.